2016
DOI: 10.1159/000446174
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Haemophagocytic Lymphohistiocytosis Associated with Maternal Adult-Onset Still's Disease

Abstract: Neonatal haemophagocytic lymphohistiocytosis (HLH) is a rare but potentially lethal condition. We recently encountered a preterm infant who developed severe HLH associated with maternal adult-onset Still's disease, which to our knowledge has not been previously reported. The infant presented with fever, generalised lymphadenopathy, transient erythematous skin rash, hepatosplenomegaly, ascites, pancytopenia, marked hyperferritinaemia, and hypofibrinogenaemia, which were features similar to maternal presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Autoantibodies, antigens and inflammatory mediators can trigger inflammation (29,30). Although circulating autoantibodies have been detected in patients with HlH (29,31), to the best of our knowledge, there have been no reports of endogenous anti-iFn-γ igG production in the context of HlH pathogenesis. in preclinical trials, neutralizing Figure 6.…”
Section: Discussionmentioning
confidence: 97%
“…Autoantibodies, antigens and inflammatory mediators can trigger inflammation (29,30). Although circulating autoantibodies have been detected in patients with HlH (29,31), to the best of our knowledge, there have been no reports of endogenous anti-iFn-γ igG production in the context of HlH pathogenesis. in preclinical trials, neutralizing Figure 6.…”
Section: Discussionmentioning
confidence: 97%
“…Her condition improved with immunosuppressive therapy and the fetus was delivered prior to treatment. There are also two cases reported of neonatal HLH associated with maternal AOSD 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…(6) The leukocytes in the hydrothorax show inflammatory changes, in which neutrophils are increased predominantly. (7) The ESR is shown to increase. (8) Bone marrow examination shows infectious foci.…”
Section: Laboratory Examinationmentioning
confidence: 96%
“…However, based on few studies and case reports, little is actually known about the pregnancy outcome and neonatal outcome of AOSD patients with pregnancy, especially the impact of different medications during pregnancy on them. In particular, Anna Lin et al [7] reported case of neonatal hemophagocytic syndrome associated with maternal AOSD for the first time in 2016. The infant they reported was seemingly normal apart from mild prematurity at birth.…”
Section: Relationship Between Aosd and Pregnancy Outcomementioning
confidence: 99%
See 1 more Smart Citation